Consumption and youth employment impact on production of Bulgarian organic products - Georgi Aleksiev; Dora Doncheva; Konstantin Stoyanov; Konstantin Stankov (The Central European Review of Economics and Management (CEREM), 2019)
During the current planning period of the Common Agricultural policy of the European Union, a newly formed Bulgarian organic production sector has rapidly developed. In the span of just three years - from 2014 to 2017 Bulgaria has risen to the top of the EU organic production charts for several products (mainly aromatic oils and honey). This was in part a result of a significant institutional support from CAP and the local government. The production has grown rapidly but the same cannot be said about the local organic food market. Consumers have severe reservations towards organic products, their higher prices and lack of confidence towards their quality and certification.Aim: To analyze the dynamics of production of Bulgarian organic products and the local organic food market in order to assess its sustainability.Design / Research methods: The methods used to solve the tasks are: analysis and synthesis, systematic and structural approach, statistical calculations. This study analyzes data from centralized sources as well as from own research.Conclusions / findings: There is still not enough bio-food processing plants in the country and with the necessary capacity to meet the local market needs. This has led to a clear export orientation of local bio products. Over the last two years, the construction and certification of processing facilities in the sector have begun and they are most often the result of foreign investment. Adding value to Bulgarian bio products is important for their recognition and trust by local consumers as well as those on international markets.Originality / value of the article: The underlined correlation between production and consumption of organic products in Bulgaria has never been fully researched.
Keywords: Q10; Q1; Q13; 330; bio-products; market; support; competitiveness